2004
DOI: 10.2174/0929867043365323
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress and Cell Signalling

Abstract: An increasing body of evidence from animal models, human specimens and cell lines points to reactive oxygen species as likely involved in the pathways, which convey both extracellular and intracellular signals to the nucleus, under a variety of pathophysiological conditions. Indeed, reactive oxygen species (ROS), in a concentration compatible with that detectable in human pathophysiology, appear able to modulate a number of kinases and phosphatases, redox sensitive transcription factors and genes. This type of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
387
0
15

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 639 publications
(418 citation statements)
references
References 347 publications
(418 reference statements)
9
387
0
15
Order By: Relevance
“…On the other hand, it has been shown that ROS play important roles in somatic cell functions such as cell proliferation and differentiation [21,45]. Consistent with the previous finding, our results showed that increase in concentration of ALA lead to decrease ROS concentration which in turn results in decrease follicles size, survival rate, and developmental competence.…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, it has been shown that ROS play important roles in somatic cell functions such as cell proliferation and differentiation [21,45]. Consistent with the previous finding, our results showed that increase in concentration of ALA lead to decrease ROS concentration which in turn results in decrease follicles size, survival rate, and developmental competence.…”
Section: Discussionsupporting
confidence: 92%
“…In low intracellular concentrations, ROS act as secondary messengers in signal transduction pathways regulating cell growth, while high ROS concentrations induce cellular senescence and apoptosis by oxidising nucleic acids, proteins, and lipids (Poli et al 2004). In normal conditions, a dynamic balance between ROS generation and scavenging exists, resulting in a relatively low level of ROS maintained within cells.…”
Section: Introductionmentioning
confidence: 99%
“…With distinctive demonstration of the involvement of reactive oxygen species (ROS) and reactive nitrogen species (RNS) in human physiology [8,10,24,[37][38][39][40][41][42][43][44][45], the concept of ''Toxic molecules'' for free radicals FR is now outdated. In fact, there is a strong doubt if there is any acute phase FR generation is involved in etiopathogenesis of human diseases; that raised oxidative stress (OS) in majority of the disease is consequence and not the cause [6-8, 12, 18, 46-48] that raised OS is not present in all the patients [3,5,14,[49][50][51] and that a specific level of OS is necessary for vital activities [43,52,53].…”
mentioning
confidence: 99%